2018
DOI: 10.1016/j.wjorl.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Taste acceptability of thickening agents

Abstract: ObjectivePatients with dysphagia are often unable to manage secretions and liquids, necessitating the use of commercial thickeners to decrease the likelihood of aspiration. This study aims to evaluate the effect of commercially available thickeners on hedonic perception of various liquids.MethodsForty subjects without preexisting dysphagia or anosmia were recruited from a tertiary care otorhinolaryngology clinic over a five-month period. Participants were presented with samples of three unthickened liquids (ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…FCT presented very good rheological properties, as it was resistant to α-salivary amylase, which demonstrated that viscosity remained constant in the oral cavity, increasing the therapeutic value of FCT compared with thickeners composed just by starch. The low adherence of patients to fluid modification is due to the low palatability of those products at high viscosity levels [ 46 ]. The basal palatability of this product was quite good and surprisingly, the palatability analysis performed showed no significant differences between liquid (<50 mPa·s) and the thickened viscosities (250-2000 mPa·s).…”
Section: Discussionmentioning
confidence: 99%
“…FCT presented very good rheological properties, as it was resistant to α-salivary amylase, which demonstrated that viscosity remained constant in the oral cavity, increasing the therapeutic value of FCT compared with thickeners composed just by starch. The low adherence of patients to fluid modification is due to the low palatability of those products at high viscosity levels [ 46 ]. The basal palatability of this product was quite good and surprisingly, the palatability analysis performed showed no significant differences between liquid (<50 mPa·s) and the thickened viscosities (250-2000 mPa·s).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our results, both natural and gum‐based thickeners were preferred over the starch‐based thickener in hot chocolate (Horwarth et al., 2005). It seems, however, that sweet thickened beverages are better accepted (Horwarth et al., 2005; Yver, Kennedy, & Mirza, 2018). Similar to our results, Ferry et al.…”
Section: Discussionmentioning
confidence: 99%
“…Since the patient's fluid intake may be reduced because of the need for thickening liquids associated with the decreased palatability of these products, constipation can emerge as a complaint by patients using thickening agents . Xanthan gum thickeners can be seen as an important source of soluble fiber for these patients and potentially improve constipation …”
Section: Discussionmentioning
confidence: 99%